Drought Occurrence in Central European Mountainous Region (Tatra National Park, Slovakia) within the Period 1961–2010 - Jaroslav Vido; Tsegaye Tadesse; Zbyšek Šustek; Radoslav Kandrík; Miriam Hanzelová; Jaroslav Škvarenina; Jana Škvareninová; Michael Hayes (Advances in Meteorology)
Drought has recently become a significant topic in the Central European region. It has been observed that the drought phenomenon has severe impacts on the agriculture, hydrology, social, and economic sectors of lowland areas. This study focuses on how drought, defined as a precipitation shortage, occurs in higher altitudes of the Tatra National Park (Tatra Mts., Slovakia), which is a significant biological reserve of the Central European fauna and flora. The main goals of this research include identifying drought variability and its characteristics over the Tatra National Park in the West Carpathians (Slovakia), especially to characterizing drought variability and its spatial pattern across the Tatra National Park from 1961 to 2010 using the Standardized Precipitation Index (SPI) and standard Geographic Information System (GIS) methods. The results showed that frequency of drought occurrence has cyclic pattern with approximately 30-year period. The spatial analyses showed that precipitation shadow of the mountains influences the risk of drought occurrence. The drought-prone areas over the mountains are also identified.